Soil Improvement of Petobo Silty Sand using Ferronickel Slag and Alkaline Activators - Aswin Lim; Adrianus Renaldy; David Kristian (Applied Research on Civil Engineering and Environment (ARCEE), 2023)
This study aims to provide an alternative soil improvement that can be applied in the Petobo area, which experienced liquefaction on September 29, 2018. Ferronickel slag is utilized as a binding agent. Furthermore, large concentrations of alkaline solutions (potassium hydroxide and sodium hydroxide) are utilized as activators to activate kaolin and initiate the geopolymer production process. From the test results, it can be concluded that sodium hydroxide and potassium hydroxide solutions are effective to be applied as an alkaline solution. The maximum unconfined compressive strength of the sample is about 530 kPa with a concentration of 10% of ferronickel slag and 10M of alkaline activator. This value is twice larger than if we applied cement to the soil with the same amount of concentration. Hence, the effect of the admixture of ferronickel slag and alkaline activator is more dominant than the admixture of cement only. Furthermore, the Scanning Electron Microscope and X-Ray Fluorescence Spectrometer tests were also carried out to investigate the chemical bonds that occurred in the samples. It is revealed that the geopolymer matrix envelops soil particles resulting from the geopolymer reaction. The composition of SiO2 and Al2O3 in the treated Petobo silty sand decreased. It might be due to the geopolymer reaction that occurs in the sample so that the content of SiO2 and Al2O3 compounds is reduced. Because it uses an activator in the form of a KOH and NaOH solution, there is an increase in the levels of MgO compounds in the sample compared to untreated Petobo silty sand.